Line manager implementation and employee HR attributions mediating mechanisms in the HRM system—Organizational performance relationship: A multilevel and multipath study. (31st October 2020) - Katou, Anastasia A.; Budhwar, Pawan S.; Patel, Charmi
Abstract: Drawing on the attribution and social exchange theories, this study by proposing an integrated multilevel and multipath framework examines the impact of HRM content on organizational performance, through the serially mediating mechanisms of HR strength, line manager HR implementation, and employee HR attributions. Using a sample of 158 Greek private organizations and having data from senior managers, line managers, and employees, we conducted a multilevel path analyses via Mplus. We found that between organizations (a) HR strength fully mediates the relationship between HRM content and line manager HR implementation, (b) line manager HR implementation fully mediates the relationship between HR strength and employee HR attributions, and (c) employee HR attributions fully mediate the relationship between line manager HR implementation and organizational performance. Accordingly, this study advances prior knowledge by examining an integrated research pathways framework that has largely been investigated in isolation.